PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS IV TEMA 7 INDAHNYA KEBERAGAMAN DINEGERIKU DI SD NEGERI 091254 BATU ONOM - Yosindi Tamaro Aruan; Rio Parsaoran Napitupulu; Eva Pasaribu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to investigate the effect of the Make a Match learning model on the learning outcomes of grade 4 students on theme 7